The Distribution of the Antarctic Limpet Nacella concinna (Nacellidae) on Underwater Landscapes of the Meek Channel, Argentine Islands, Graham Land - Berezkina, A.E.; Shrestha, M.Yu.; Sinna, O.I.; Shmyrov, D.V.; Utevsky, A.Yu. (Український антарктичний журнал, 2018)
Objective(s). To clarify the patterns of Nacella concinna (Nacellidae) distribution in the water area of the Argentine Islands Archipelago (Meek Channel). Morphometric, statistical, cartographic methods as well as geoinformation technologies were used.